Serotipe Virus Dengue dan Populasi Aedes aegypti dan Aedes albopictus (Diptera: Culicidae) Di Kota Bengkulu - Dessy Triana; Sitti Rahmah Umniyati; Budi Mulyaningsih; Munauwarus Sarirah (Berita Kedokteran Masyarakat (BKM), 2018)
Dengue virus serotype and the population of Aedes aegypti and Aedes albopictus in Bengkulu City: its implications for dengue prevention programs Purpose: This study aimed to prevent the development of dengue virus by detecting dengue virus serotypes of Aedes aegypti (Ae. aegypti) and Aedes albopictus (Ae. albopictus) and to determine the population of Ae. aegypti and Ae. albopictus in dengue endemic area (Sidomulyo Village) and dengue sporadic area (Tanjung Jaya Village) in Bengkulu City, Indonesia. Methods: The design of study was observational-analytic. Aedes sp eggs were collected by ovitraps from Sidomulyo and Tanjung Jaya Villages. The eggs were reared to adult and identified to determine of Ae. aegypti and Ae. albopictus. Identification of species Ae. aegypti and Ae. albopictus uses the pictorial key for the identification of mosquitoes by Rueda. Detection of dengue virus serotypes were done by RT-PCR and nested PCR method using specific primers Lanciotti. Results: The Serotypes of dengue virus of Ae. aegypti in dengue endemic and sporadic areas were dengue-3 (DENV-3) and the serotypes of dengue virus of Ae. albopictus in dengue sporadic area was dengue-3 (DENV-3). The population ratio of Ae. aegypti and Ae. albopictus in dengue endemic area (61%:39%) and dengue sporadic areas (27%:73%), respectively. Conclusions: Aedes aegypti in dengue endemic and sporadic areas and Ae. albopictus in dengue sporadic area has potential as a dengue-3 vector. Health Agency of Bengkulu City could optimize the prevention program of dengue and activate the Jumantik cadres.AbstrakTujuan: Penelitian ini bertujuan untuk pencegahan perkembangan penyakit DBD dengan mendeteksi serotipe virus dengue pada nyamuk Ae. aegypti dan Ae. albopictus dan menentukan rasio populasi nyamuk Ae. aegypti dan Ae. albopictus di daerah endemis dan sporadis DBD di Kota Bengkulu. Metode: Desain penelitian ini adalah observasional-analitik. Telur nyamuk Aedes sp dikumpulkan menggunakan ovitrap dari daerah endemis DBD (Kelurahan Sidomulyo) dan daerah sporadis DBD (Kelurahan Tanjung Jaya). Identifikasi spesies Ae. aegypti dan Ae. albopictus menggunakan pictorial key for the identification of mosquitoes Rueda. Deteksi serotipe virus dengue dilakukan dengan metode RT-PCR dan Nested PCR menggunakan primer spesifik Lanciotti. Hasil: Serotipe virus dengue yang ditemukan pada Ae. aegypti adalah DENV-3 (daerah endemis dan sporadis DBD) dan DENV-3 pada Ae. albopictus (daerah sporadis DBD). Perbandingan populasi Ae. aegypti dan Ae. albopictus pada daerah endemis dan sporadis DBD berturut-turut adalah (60,51%:39,49%) dan (27,08%:72,92%). Simpulan: Aedes aegypti di daerah endemis dan sporadis DBD serta Ae. albopictus di daerah sporadis DBD berpotensi sebagai vektor dengue-3. Dinas Kesehatan Kota Bengkulu dapat mengoptimalkan program pencegahan DBD dan mengaktifkan kader Jumantik.